Vertical Relations, Pass-through, and Market Definition: Evidence from Grocery Retailing - Justus Haucap; Ulrich Heimeshoff; Gordon J. Klein; Dennis Rickert; Christian Wey (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We examine how different pass-through rates, from input- to final consumer prices, and different vertical contracts affect upstream market definition. Our theory model predicts that, under reasonable conditions, higher pass-through rates lead to definitions of larger upstream markets. Data from grocery retailing is used to quantify the empirical implications of our theoretical result. We find that resale price maintenance leads to larger upstream market definitions than linear pricing models. The reason is that linear pricing contracts are associated with lower pass-through rates under imperfect competition. We therefore advise competition authorities to carefully model vertical market structures, whenever they expect incomplete pass-through to be important.
Keywords: L10; L40; L80; C50; 330; market definition; vertical relations; pass-through; structural models